‘To Be or Not To Be a Cyberterrorist’, That Is the Question! The Political Communication of al-Qaeda and Islamic State on Social Networks - Belim, Célia (2017)
The digital political communication developed by terrorists, analysing two cases, al-Qaeda and Islamic State of Iraq and Syria (ISIS), is the main focus of this article. It is, concretely, explored, in the context of communication strategy, the use of social networks, in terms of the message evoked by these terrorist groups of modern times. Being an applied study with empirical techniques, such as content analysis and semiotic analysis, the major aim is founded, generally, in deconstructing and reconstructing the social networks communication strategies (objectives, means, message, target audience) of the terrorist groups and, deeply, in scrutinizing the content and form of message. The data collection comprises political messages of the terrorist groups in a digital approach. To theoretically enrich the investigation, it is adopted the framework of uses and gratifications. Results highlight that, thematically, “context codes” and “communication tools” are the most present in tweets related to both groups. Other issues expose the intention to build a belligerent and warmongering ambience. Propagandistically, “strength mood” and “dissuasion” are salient, suggesting an image of dominance. “Holy war” as the major claim in tweets corroborates the ideological frame: the alliance between religion and belligerence. The videos analysed broadly convey counterpropaganda (inter and extra terrorist groups) and instigation to war, but not much claims (one in five videos), and are based on form techniques.